E-049 Accuracy of non-invasive and invasive imaging in identifying ica occlusion: a comparative study in 65 patients. (23rd July 2017) - Mekabaty, El; Hao, Q; Cheng-Ching, E; Hussain, S; Spiotta, A; Hui, F
Abstract : Introduction: Internal carotid artery (ICA) occlusion is often encountered in acute stroke patients with reported prevalence of approximately 24% [1]. Such occlusion is usually defined preprocedural on non-invasive imaging (CT or MR angiography "CTA/MRA") if available or intraprocedural during endovascular stroke treatment (digital subtraction angiography "DSA"). However, there is discrepancy between the site of the ICA occlusion on CTA/MRA compared to DSA [2] and even to findings on endovascular intervention ( i.e. catheterization of the ICA). On imaging, a tapered narrowing of the ICA, the so-called "flame-shaped" occlusion is commonly seen [3, 4]. ICA pseudo-occlusion is therefore defined as non- opacification of the ICA on CTA/MRA but presence of flow on DSA. In our study we aim to examine the accuracy of different imaging modalities in accurately localizing the site of the ICA dissection, compared to direct catheterization of the ICA. Methods: We performed a retrospective analysis of acute stroke patients undergoing endovascular stroke treatment who exhibited ICA occlusion in 4 participating centers between January 2015 and March 2017. All patients had imaging studies (CTA or MRA), diagnostic DSA and endovascular intervention. Patients' demographics and comorbidities were noted. Images were reviewed by the interventional team in their respective center for the following parameters; extent of ICA occlusion (proximal contrast opacification cutoff and distal appearance of contrast opacification) and "flame shaped" pattern of ICA occlusion on imaging (CTA/MRA/DSA) as well as level of contrast opacification and pattern of ICA occlusion ("flame shaped", "stump" occlusion or intraluminal defect) during the endovascular intervention. Results: A total of 65 patients satisfied the inclusion criteria. The mean age was 70 years (standard deviation "SD" 13). There were 33 (51%) males and 32 (49%) females. Sixty (92%) patients had hypertension, 49 (75%) had hyperlipidemia, 23 (35) had coronary artery disease and 18 (28%) patients had diabetes mellitus. Flame- shaped occlusion pattern of the ICA was present in 12 (18%%) of patients on CTA/MRA and in 19 (29%) on DSA. Only 2 (3%) patients had ICA dissection though. During the ICA catheterization the site of the occlusion was at the common carotid artery in 1 (2%) patient, ICA origin in 13 (43%), cervical ICA in 28 (43%), petrous ICA in 2 (3%), cavernous ICA in 3 (5%), supracliniod ICA in 11 (17%), communicating segment ICA in 2 (3%) and ICA T-segment in 5 (8%) patients, while 29/57 (51%) of patients had "stump" ICA occlusion pattern, 13/57 (23%) had a "flame shaped" occlusion, 11/57 (19%) had a filling defect in the ICA and 4 (7%) patients had delayed opacification of the ICA. Conclusion: Our result suggests that there is a lack of correlation between the imaging findings of carotid occlusion on imaging compared with catheter angiography of the ICA during the intervention in acute stroke treatment. Thus, endovascular catheterization of the ICA is often required for the exact characterization and localization of the carotid occlusion and to determine if a dissection is the underlying pathology in such cases. Disclosures: A. El Mekabaty: None. Q. Hao: None. E. Cheng-Ching: None. S. Hussain: None. A. Spiotta: None. F. Hui: None.